Fluoride release and antibiofilm of Alkasite restorative materials - Obaees, Rouaa K; Alkhalidi, Emad F; Hamdoon, Suhad M (Edelweiss Applied Science and Technology, 2024)
This invitro study assessed fluoride ion release and antibiofilm activity of Alkasite materials against two types of bacterial spp. (Streptococcus mutans and Lactobacillus plantarum). Three different ion-releasing materials (Cention N, Cention Forte and Fuji IX GP) were used to make four groups. A total of 96 disc-shaped samples were prepared in polyethene mould, 32 samples (n=8) were used for evaluating fluoride ion release the samples were placed in vial containing 5ml of deionized water, and the measurements were recorded in four periods (1,7,21 and 28) days by utilizing an ion-selective electrode (ISE). 64 samples were used to evaluate the anti-biofilm activity of the materials groups against (S. mutans and L.plantarum), by using crystal violet assay for quantitative biofilm assessment (n=5 of each group for each bacterial spp.) and by SEM for the qualitative evaluation (n=3 of each group for each bacterial spp). Fuji IX GP registered the highest amount of fluoride release on 1st day of the observation period than Cention N and No primer was added to Cention Forte. On the 28th day, Primer added Cention Forte recorded the highest mean value of fluoride release among all of the groups. Primer-added Cention Forte has significantly more biofilm accumulation of both (Streptococcus mutans and Lactobacillus plantarum) than Cention N and No primer-added Cention Forte. Fuji IX showed significantly higher Streptococcus mutans biofilm accumulation compared to Cention N. Alkasite restorative materials showed a low potential for biofilm accumulation regarding both Streptococcus mutans and Lactobacillus plantarum.